Biological Anthropology Applications and Case Studies - Vovlas, Alessio (IntechOpen, 2021)
This volume provides an overview of biological anthropology, specifically in bioarchaeology, paleopathology, and forensic anthropology. It is an important resource for the scientific community that belongs to this discipline, including evolutionary biologists, ecologists, medical researchers, and students.